2019
DOI: 10.1186/s12944-019-0991-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of lipid profile in the Lebanese pediatric population

Abstract: BackgroundFew studies looked at the prevalence of dyslipidemia in pediatric Middle-Eastern countries. In addition, worldwide longitudinal changes of lipid profile is not well documented. The purpose of this study is to look at the longitudinal changes of lipid parameters in Lebanese school-age children.Materials and methodsA total of 97 subjects (41 girls and 56 boys) aged between 11 and 21 years were included in this study. The subjects were selected among 339 school-age children with a previous abnormal lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…We also interestingly found in post-menarchal girls, a significant positive correlation between serum PCSK9 levels and TC, LDL-C, and non-HDL-C a finding not observed in premenarchal girls. This finding can be explained by the change in lipid profile with age as we previously reported in the same cohort [24]. In this study, we found that 53.6% of school children have normalized their abnormal lipid profile after a 3-years follow-up.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We also interestingly found in post-menarchal girls, a significant positive correlation between serum PCSK9 levels and TC, LDL-C, and non-HDL-C a finding not observed in premenarchal girls. This finding can be explained by the change in lipid profile with age as we previously reported in the same cohort [24]. In this study, we found that 53.6% of school children have normalized their abnormal lipid profile after a 3-years follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…Dyslipidemia is highly prevalent in Lebanon in both adults [21,22] and children [19,23,24]. In our previous study, we found that the prevalence of high non-HDL-C, high TG, and high Lp(a) in Lebanese school children are, respectively, 9.2%, 26.6%, and 14.4% [23,24]. However, PCSK9 has never been measured in Middle Eastern pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated an association between lifestyle factors and cholesterol levels in children, suggesting the significance of nutritional knowledge, behavior, and physical activity for the maintenance of cholesterol levels within the reference range [2,12,[25][26][27][28]. Moreover, an association between obesity and dyslipidemia has been observed in pediatric populations [22].…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with results from a study conducted in Lebanon, where a high proportion of school-age children (53.6%, 52/97 children) were found to normalize their abnormal lipid profile after 3 years. 27 However, it is important to note that these 97 Lebanese children who had a follow-up lipid profile after 3 years were from an original study group of 339 children with an abnormal lipid profile, meaning that the longitudinal group represented only 28.6% of those with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%